Multi-Sector Collaboration in Community Empowerment: Study on the Partnership between the Regional Government and the Community Empowerment Institution LPM Sriwijawa - Lestari, Aprilia; Anggara, Ikang Putra; Anita, Ema (Universitas Muhammadiyah Sorong, 2024)
Community empowerment can be seen from various aspects, both economically, socially, and even from the existence of the community in the decision-making process. Empowerment now cannot only rely on a helping hand from the government alone, the dynamics of society that continue to occur make the government's function in this sector often neglected. Therefore, collaboration from various actors is essential in implementing community empowerment, one of which is collaboration with non-governmental organizations. The purpose of this study is to analyze the role of multi-sectors, especially NGOs and local governments in empowering communities in Ogan Komering Ulu Regency. The type of research used in this study is qualitative. Researchers obtained data in three ways, namely through observation, interviews, and documentation. The local government has established collaboration with the Sriwijaya Community Empowerment Organisation (LPM) to carry out community empowerment functions in the Ogan Komering Ulu district. As a result, the government is greatly helped by the programs conducted by LPM Sriwijaya in several villages and sub-districts. In this collaboration, the local government plays a policy maker and provides funding for several programs, while LPM Sriwijaya as a non-governmental organization acts as an implementing actor who assists and provides direct support in the community of Ogan Komering Ulu Regency